Solutions for diffusion equation - DOI: 10.4025/actascitechnol.v31i1.2838 - Lenzi, Ervin Kaminski (2009)
This work is devoted to investigate solutions for the diffusion equation with a nonlocal spatial and time dependent term by using the Green function approach. This nonlocal term incorporated in the diffusion equation may be related to a several physical contexts, in particular, with the fractional spatial and time derivatives and reaction processes. It also introduces different regimes for the diffusion process and may be connected to a rich class of anomalous diffusive processes.